Shortened 8-Week Course of Sofosbuvir/Ledipasvir Therapy in Adolescents With Chronic Hepatitis C Infection. Issue 5 (November 2019) - Serranti, Daniele; Dodi, Icilio; Nicastro, Emanuele; Cangelosi, Antonina M.; Riva, Silvia; Ricci, Silvia; Bartolini, Elisa; Trapani, Sandra; Mastrangelo, Greta; Vajro, Pietro; D'Antiga, Lorenzo; Resti, Massimo; et al.
Abstract : ABSTRACT: Treatment-naïve, noncirrhotic adults with chronic hepatitis C virus genotype 1 infection and with viremia levels <6 million IU/mL could be effectively treated with sofosbuvir/ledipasvir for 8 weeks. The aim of this pilot, prospective, open-label, multicenter study was to evaluate the efficacy and safety of this shortened treatment course in adolescents (≥12 years). The efficacy endpoint was sustained virological response 12 weeks after the end of treatment. Safety was assessed by adverse events and clinical/laboratory data. Fourteen consecutive adolescents (median age 16.5 years, Q1 14.1–Q3 17.4; female 57.1%), vertically infected, were enrolled and treated (June 2018–January 2019). Overall, the end of treatment response and sustained virological response 12 weeks after the end of treatment were 100%. No grade 3 to 4 adverse event or a serious adverse event was observed. Further studies are needed to confirm the optimal efficacy of the shortened 8-week treatment with sofosbuvir/ledipasvir for treatment-naïve, noncirrhotic adolescents with chronic hepatitis C virus genotype 1 infection and pretreatment viremia level < 6 million IU/mL.